(untitled) (TSUL LEGAL REPORT, 2026)
This study examines the phenomenon of cybercorruption–the use of digital technologies to carry out corrupt practices–in the context of the Central Asian region. The purpose of the study is to analyze the essence of cybercorruption, identify key manifestations of this phenomenon, and develop recommendations to counter this threat. The research methodology is based on a comprehensive analysis of the legal framework for cybersecurity and anti-corruption, a comparative study of international experience, and the systematization of recommendations from international organizations. The results indicate the growing vulnerability of the region to cybercorruption due to the insufficient adaptation of legal systems to digital transformation, the limited capacity of law enforcement agencies, and inadequate regional coordination. The proposed recommendations include improving the legal framework, developing institutional mechanisms, and expanding regional cooperation to effectively prevent and suppress cybercorruption. The presented analysis is important for the formation of a comprehensive policy to ensure digital security and transparency in Central Asia.